Penegakan Aturan Hukum Melalui Otoritas Jasa Keuangan (OJK) Terhadap White Collar Crime Insider Trading Dalam Pasar Modal - Sulubara, Seri Mughni; Murthada; Amrizal (Jurnal Ilmiah Penegakan Hukum, 2023)
This research aims to determine the enforcement of legal regulations through the Financial Services Authority (OJK) against white collar crime insider trading in the capital market. Law enforcement in insider trading cases includes three things, namely administrative, civil and criminal enforcement. In carrying out investigations, the OJK is given special authority as an investigator as intended in the Criminal Procedure Code. The research method used is normative legal research which uses a conceptual approach and the nature of this research is analytical descriptive. Based on Law Number 21 of 2011, enforcement of legal regulations carried out by the Financial Services Authority (OJK) regarding white collar crime insider trading in the capital market is by conducting inspections and investigations. OJK, with its authority as an audit agency, can take action against parties suspected of violating regulations in the capital markets sector, and the OJK has the authority to search for, collect and process data or other information indicating whether there has been a legal violation in the marketing sector. In addition, the OJK as an investigative agency can carry out investigative actions against business entities in the capital markets sector that are suspected of committing criminal law violations, are suspected of causing or incurring losses in the capital market or certain units, or as a whole.